Effectiveness of healthy organization by participatory encouragement (hope) project on reducing cardiovascular risk factors in employees of the electric generating authority of Thailand (EGAT) - Pajaree Abdullakasim (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2012